The Effect of Workload, Discipline and Work Safety on the Performance of Employees of the Padang City Civil Police Unit (SATPOL PP) - Amrullah, Amrullah; Vika Fajriani (ADPEBI, 2024)
In today's era of uncertainty, various challenges arise in efforts to manage human resources in the governmentsector, where human resource management (HRM) holds an important battle in the success and efficiency of theimplementation of public services in the government environment. The purpose of this study is to determine the influenceof Workload, Discipline and Work Safety on the Performance of Employees of the Padang City Civil Police Unit(SATPOL PP). Satpol PP in the Padang City area, West Sumatra. The type of research used in this study is associativeresearch with a quantitative approach. The population in this study is all Contract Employees (No PNS) in the Padang CityCivil Service Police Unit (SATPOL PP). The sample in this study amounted to 80 respondents. The technique of collectingresearch data through questionnaires uses a Likert scale. The data analysis technique in this study is multiple linearregression.Based on partial statistical analysis of the Workload variable with a tcount value of 3.283 > ttable 1,665 with avalue (Significant = 0.008 <0.05) This means that the workload has a positive and significant effect on the performanceof the Employees of the Padang City Civil Police Unit. Work Discipline Variable (X2) with a tcount value of 2.084>ttable1,665 with a value (Significant = 0.041 <0.05) This means that Work Discipline has a positive and significant effect onthe Performance of Employees of the Padang City Civil Police Unit. Occupational Safety Variable (X3) with a calculatedvalue of 2.183> ttable 1.665 with a value (Significant = 0.048 <0.05) This means that occupational safety has a positiveand significant effect on the performance of employees of the Padang City Civil Service Police Unit.The result of F that the value of Fcal> Ftable with a value of 1.463 > 3.1 respectively with a significant value of(0.031) < 0.05 which means that Workload, Discipline and Occupational Safety simultaneously or together have asignificant positive effect on the Performance of Employees of the Padang City Civil Police Unit (SATPOL PP).